Apakah pendapatan asli daerah (PAD) mendorong ketimpangan distribusi pendapatan di Yogyakarta? - Dessy Rachmawatie (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
Paradigm Development is a process in development to achieve a change. Inequality of income distribution is a problem that is quite a severe concern in all regions and developed and developing countries. This proves that Yogyakarta Province still has a relatively high level of inequality in income distribution. Problems in income distribution inequality can be influenced by various factors, such as Regional Original Income to income distribution inequality in 5 Regencies/Cities in Yogyakarta Province for the 2010-2020 period. This study uses secondary data with panel data analysis method with a period of 2010-2020, using the Fixed Effect Model approach. This analysis shows that Regional Original Income has a positive and significant influence on the inequality of income distribution in 5 regencies/cities in Yogyakarta Province.